Numerical investigation of thermal losses from air filled annulus of a parabolic trough solar collector / Alhassan Salami Tijani and Muhammad Jaafar Jamarei - Alhassan Salami Tijani; Muhammad Jaafar Jamarei (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2016)
Solar energy has the potential to meet the growing need for global energy consumption. In recent times there is large number of solar energy systems developed, one of such widely used technology is parabolic trough collector (PTC). The PTC technology is one of the successful technologies because it is the most mature and one of the least expensive. PTC receivers with air filled annuli are used mainly for high temperature applications such as food processing industry. This is due to the fact that they are less costly but on the other hand they have high heat loss as compared to vacuum receivers. One of the techniques that can be adopted in order to enhance the thermal performance of the PTC has been discussed in this work. An insulation fiberglass with high heat resistant was inserted into the portion of the receiver annulus that does not receive concentrated sunlight. This study focuses on the calculation of conduction and convection heat losses of the half insulated annulus part only. The performance of the proposed concept was then compared to conventional receiver with air filled annulus. The effect of wind speed and mass flow rate of the working fluid was also considered. The reason for using mass flow rate and wind speed as manipulated variable is because both parameters affect the thermal loss of the system. The results shown that the heat loss from the half insulated is smaller compared to the heat loss from air annulus receiver by 70% depending on the wind speed of the location. Therefore, the proposed receiver is expected to be most suitable replacement for receivers with air annulus.